PENERAPAN PARIWISATA BERKELANJUTAN DI CEKING TEGALLALANG, GIANYAR - Yudi Surya Prananda, I Wayan; Alam Paturusi, Syamsul (JURNAL MASTER PARIWISATA; Volume 04, Nomor 02, Januari 2018DO - 10.24843/JUMPA.2018.v04.i02.p08, 2018)
The purpose of this article is to formulate management strategies in realizing sustainable tourism in the tourist attraction of Ceking Rice Terrace, Tegallalang, Gianyar. Data were collected through direct observation, depth interview, questioner and library study and analyzed by using qualitative descriptive analysis, IFE, EFE, IE, SWOT, and QSPM matrix. The analysis shows that the general strategy that must be done to realize sustainable tourism in the tourist attraction of Ceking Rice Terrace is a growth strategy through product development by di erentiating and innovating products in the form of seasonal packages such as rice planting packages for tourists, plowing rice elds, understanding local wisdom such as subak irigation system and promoting prewedding photos shoot around the tourist attraction. The results of SWOT and QSPM matrix analysis show that there are nine alternative strategies with priority scale that must be done including con ict management, evaluation of compensation, environmental restructuring, professional management implementation, and improving service quality.